PENDEKATAN ANTROPOLOGI DALAM STUDI LIVING HADIS DI INDONESIA: Sebuah Kajian Awal - Jajang A Rohmana (Holistic al-Hadis, 2015)
Hadith studies in Indonesia continually try to be developed by scholars. They try to develop the hadith studies which have been considered “rarely studied” compared to other Islamic studies. One of the issues uses a multidisciplinary approach involving the social sciences and humanities. The phenomenon of living hadith is part of the issues. It tried to shift the focus which is not only study the text of hadith, but also shifted to the issues of hadith in practice, such as socio-cultural phenomenon that live and thrive in the community. The object study of living hadith is the community who receive, use and practice the hadith in their daily lives. One of approaches that uses to research the community is anthropology. It is a scientific disciplines seen from the aspect of human culture. This paper is a preliminary studies on the importance of using anthropological techniques in the study of living hadith in Indonesia. It will focus on the issue of the development of living hadith in Indonesia, the importance to shift the hadith studies from the text to the public sphere, the development of the study of living hadith from the great tradition to the little tradition, the use of anthropology as an approach or perspective and the methodological steps in the anthropological studies of living hadith. This study is important not only in order to expand the area of hadith studies towards a more dynamic knowledge, but is also expected to strengthen the basis of arguments about the importance of living hadith in the discourse of the anthropology of Islam.